Persepsi Petani Karet Terhadap Tauke (Studi Kasus Hubungan Patron-Klien Petani Karet dan Tauke) di Desa Kasang Limau Sundai Kecamatan Kuantan Hilir Kabupaten Kuantan Singingi - Gervilon Darvis; Fajar Restuhadi; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research was conducted in Kasang Limau Sundai village, Kuantan Hilir District, Kuantan Singingi Regency . Intake of respondents in this study conducted with (Simple purposive sampling). The methods taked of data used  descriptive analysis, Cartesian diagram analysis, and the Spearman correlation analysis multiatribut Fishbein model of attitude . the results showed as for selling of the rubber,  the farmer must be delivery using transportation services. Atibut pay cash , make loans, fast and good service, given the high prices and the provision of THR is an attribute that must be maintained employer. For a relationship to the importance of farmer characteristics, educational characteristics obtained significantly correlated with THR attributes, characteristics of production, real income and expenditure associated with attribute, while paying cash to the characteristics of the relationship with the level of confidence is obtained that a very real life characteristics associated with the attributes of bonded labor system, the characteristics of education attributes associated with sorting, production characteristics significantly correlated with sorting attributes, characteristics of the income and expenses associated with the attributes are very real suggestion of a friend, the characteristics of farming experience significantly correlated with sorting and dealing with the very real relationship intimacy, as well as the characteristics of the land area significantly correlated with attributes suggestions of friends. Perceptions or attitudes of farmers to traders belonging to the neutral category. Patron- client relationships that occur are the result of production marketing and consumtion relationship.   Keywords: Farmer Characteristics, Perceptions/Attitude, Attributes, Patron-Client Relations, employer